Research on the Numerical Simulation of Sleeper in the Pipeline Global Buckling Controlling Practice - Liu Wen-Bin; Liu Ai-Min (ITM Web of Conferences, 2017)
This paper analyzed the lateral buckling of pipelines located in Western Africa with ABAQUS software. The application of sleepers in practice is explored to guide the pipeline buckling controlling design.